PENGARUH PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE AND SHARE TERHADAP PENGUASAAN KOMPETENSI DASAR MENGANALISIS STRATEGI NEGARA DALAM MENGATASI ANCAMAN UNTUK MEMBANGUN INTEGRASI NASIONAL DALAM BINGKAI BHINNEKA TUNGGAL IKA PADA SISWA KELAS XI SMA NEG - Rahayu, Ismi Eka; Triastuti, Rini; Suryono, Hassan (PKn Progresif, 2016)
The purpose of this study was to prove the existence of the positive effect of application search solve create and share learning model on the mastery of basic competency of analyze the state strategy in the fight threats to establish national integration in a frame of Bhinneka Tunggal Ika in the 11th graders of SMA Negeri 6 Surakarta in the School Year of 2015/2016. This research was conducted using quantitative methods experiment with models Posttest Only Control Design. The population of research was the 11th graders of SMA Negeri 6 Surakarta in the School Year of 2015/2016. The sample selected was 11th of IPS 4 grade served as experiment class and 11th IPS 3 as control class. The sampling technique using cluster random sampling. Techniques of collecting data used were observation for X variable and test for Y variable.Technique of analyzing data used was one-predictor regression analysis. The results showed that there there was a positive effect of application search solve create and share learning model (X) on the mastery of basic competency of analyze the state strategy in the fight threats to establish national integration in a frame of Bhinneka Tunggal Ika (Y) in the 11th graders of SMA Negeri 6 Surakarta in the school year of 2015/2016 as evidenced by the results the correlation coefficient where rhitung> rtabel or 0.607> 0.361 means that Ho is rejected, Ha accepted. The magnitude of the effect of variable X to Y is shown by the calculation of the contribution of determination of 31.4%. The regression equation equation = 21.785 + 1.316 X. The conclusion of this study that there was a positive effect application search solve create and share learning model on the mastery of basic competency of analyze the state strategy in the fight threats to establish national integration in a frame of Bhinneka Tunggal Ika in the 11th graders of SMA Negeri 6 Surakarta in the school year of 2015/2016